Canada in the Frame Copyright, Collections and the Image of Canada, 1895-1924 - Hatfield, Philip J. (Modern Americas, 2018)
Canada in the Frame explores a photographic collection held at the British Library that offers a unique view of late nineteenth-century and early twentieth-century Canada. The collection, which contains in excess of 4,500 images, taken between 1895 and 1923, covers a dynamic period in Canada's national history and provides a variety of views of its landscapes, developing urban areas and peoples. Colonial Copyright Law was the driver by which these photographs were acquired; unmediated by curators, but rather by the eye of the photographer who created the image, they showcase a grass-roots view of Canada during its early history as a Confederation. Canada in the Frame describes this little-known collection and includes over 100 images from it. The author asks key questions about what it shows contemporary viewers of Canada and its photographic history, and about the peculiar view these photographs offer of a former part of the British Empire in a post-colonial age, viewed from the old 'Heart of Empire'. Case studies are included on subjects such as urban centres, railroads and migration, which analyse the complex ways in which photographers approached their subjects, in the context of the relationship between Canada, the British Empire and photography.